Sensitivity to Communication Partners During Naturalistic AAC Conversations in Cantonese Chinese - Yum, Yen Na; So, Soby Ka Wing; Chan, Rosanna Yuen-Yan (Frontiers in Psychology, 2021)
Previous studies have shown that graphic-based AAC output tend to be short and simple in structure with non-canonical word order, and that AAC users may show differences when communicating with peers compared to professionals such as speech therapists. However, there was a lack of report for graphic-based AAC in the Chinese context, and the effect of communication partners had not been investigated systematically. In this study with 34 AAC users and 10 speech therapists, we reported common and distinct features of free conversations in Cantonese graphic-based AAC, relative to AAC in other languages. We also found that AAC users were sensitive to different types of communication partners. In particular, when conversing with peers, AAC users produced long messages with equal proportion of questions and responses, which suggested active and bi-directional exchanges. In conversations with speech therapists, AAC users showed high diversity in expressive vocabulary, indicating access to more semantic concepts. Results suggested that the base language and the communication partner are both influential factors that should be considered in studies of graphic-based AAC. The mobile AAC system facilitated free conversations in users with complex communication needs, affording an additional channel for social participation.